Hubungan Masa Kerja Dan Lama Kerja Dengan Nyeri Leher Pada Pembatik Di Sentra Batik Giriloyo - Yani, Fitri; Anniza, Meiza; Priyanka, Krisnawan (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 6 No 1 (2020): Volume 6 No 1 Juni 2020DO - 10.24843/JEI.2020.v06.i01.p04, 2020)
Batik makers work with static and not ergonomic sitting postures within 8 hours. If the work posture is static and not ergonomic is maintained in the long term, it will cause musculoskeletal complaints atthe neck. This   study aims to determine the relationship between years of service and duration of work and neck pain in batik makers at Giriloyo batik center. The research method was observational with cross sectional approach. Data collection techniques was a questionnaire distributed to batik makes .   The   sampling technique was purposive sampling technique. The samples in this study were batik maker at Giriloyo batik centers, totaling 89 batik makers. The results of the Spearman rank correlation test showed that there was a relationship between years of service and neck pain with r-value v =0.313 (p<0.05). The relationship between duration of and neck   pain obtained r=0.299 (p<0.005). The effect of duration of work (exp. B =1,906) was more dominant than years of service on neck pain. There is a relationship between years of service and duration of work  and neck   pain in batik makers at Giriloyo batik center. The effect of work duration is more dominant than the years of service on the occurrence of neck pain in batik makers in Giriloyo batik centers.